2008
DOI: 10.1186/1475-2875-7-118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of light microscopy and rapid diagnostic test for the detection of malaria under operational field conditions: a household survey in Ethiopia

Abstract: Background: In most resource-poor settings, malaria is usually diagnosed based on clinical signs and symptoms and not by detection of parasites in the blood using microscopy or rapid diagnostic tests (RDT). In population-based malaria surveys, accurate diagnosis is important: microscopy provides the gold standard, whilst RDTs allow immediate findings and treatment. The concordance between RDTs and microscopy in low or unstable transmission areas has not been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 11 publications
7
93
5
Order By: Relevance
“…In total, 20 RDT: microscopy studies and 13 RDT:PCR studies from the literature search met our inclusion criteria. Combined with additional data sets from DHS and unpublished studies, the pooled data available for evaluation yielded 323 pairs of prevalence estimates for RDT and microscopy 5,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48][49] and 162 pairs for RDT and PCR 25,27,34,39,40,42,[45][46][47][48][49][50][51][52][53][54][55] . The extracted proportions together with the main characteristics of the studies from our literature search are provided in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 20 RDT: microscopy studies and 13 RDT:PCR studies from the literature search met our inclusion criteria. Combined with additional data sets from DHS and unpublished studies, the pooled data available for evaluation yielded 323 pairs of prevalence estimates for RDT and microscopy 5,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48][49] and 162 pairs for RDT and PCR 25,27,34,39,40,42,[45][46][47][48][49][50][51][52][53][54][55] . The extracted proportions together with the main characteristics of the studies from our literature search are provided in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Where available, information on location, sample size, RDT brand and type (HRP2 or pLDH), age group (15 or younger compared with older than 15) and prevalence estimates were recorded 5,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Furthermore, data from the DHS online database were extracted 43 .…”
Section: Methodsmentioning
confidence: 99%
“…The present study further reported 0.7% cases of non-P. falciparum plasmodium infections within the riverine zone which were not confirmed through microscopy as they all read negative. Most of the slides which were positive on both P. falciparum and Pan bands on the SD Bioline kits were also positive by microscopy, indicating active infection unlike HRP-2 which persists in blood long after clearance of parasites [5].…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, many treated confirmed cases in Africa are lower compared to other regions of the world [4]. This suggests that majority of treated cases are clinically diagnosed yet this type of diagnosis can be unreliable due to the non-specific nature of signs and symptoms of malaria [5]. It may also lead to indiscriminate use of antimalarial drugs and compromise the required quality care for patients suffering from other diseases displaying symptoms and signs similar to those of malaria [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation